2007
DOI: 10.1017/s0022215107009747
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric and imaging characteristics of distal renal tubular acidosis and deafness

Abstract: Several types of mutations in the ATP6V1B1 gene may cause distal renal tubular acidosis and sensorineural hearing loss. Patients display a typical progressive type of hearing loss and have enlarged vestibular aqueducts, with no other abnormalities being observed on imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Enlarged vestibular aqueduct (EVA) was described in patients with recessive dRTA and SNHL, and recently, this abnormality has been associated with mutations in the ATP6V1B1 gene. 7 However, there is more and more evidence that these two recessive forms of dRTA are genetically more heterogeneous in the auditory phenotype than previously assumed. A few cases harbored ATP6V1B1 mutations without SNHL have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Enlarged vestibular aqueduct (EVA) was described in patients with recessive dRTA and SNHL, and recently, this abnormality has been associated with mutations in the ATP6V1B1 gene. 7 However, there is more and more evidence that these two recessive forms of dRTA are genetically more heterogeneous in the auditory phenotype than previously assumed. A few cases harbored ATP6V1B1 mutations without SNHL have been described.…”
Section: Introductionmentioning
confidence: 99%
“…However, only in the study of Joshua et al were several types of mutations in the ATP6V1B1 gene found to be associated with inner-ear morphological alterations and a typical progressive hearing loss. Patients had EVA, with no other abnormalities being observed on imaging [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some data from both groups had been included in previous publications [11,12,13]. We now added 8 heretofore non-published cases.…”
Section: Resultsmentioning
confidence: 99%